1994
DOI: 10.2307/1592115
|View full text |Cite
|
Sign up to set email alerts
|

Lesions Resulting from Attempted Shwartzman Reaction in Turkey Poults Inoculated with Pasteurella multocida Lipopolysaccharide

Abstract: Five-week-old turkey poults were given two consecutive intravenous injections (24 hours apart) of highly purified Pasteurella multocida lipopolysaccharide (LPS) in an effort to induce a generalized Shwartzman reaction. There were no gross lesions, and microscopic lesions were limited to focal hepatic necrosis with heterophil infiltration. Hepatic lesions did not differ qualitatively from lesions in turkeys given a single dose of lipopolysaccharide. Margination of heterophils in the pulmonary vasculature was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Lipopolysaccharide-protein complex (endotoxin) is an important constituent of the outer membrane of a P. multocida cell. Besides its toxic role in pathogenesis of the disease (Schimmel et al, 1982;Mendes et al, 1994;Kunkle and Rimler, 1998;Horadagoda et al, 2002), endotoxin is also immunogenic at low concentrations (Rimler and Phillips, 1986;Muniandy et al, 1998). LPS molecules are not toxic when they are bound to the bacterial outer membrane but after release from the bacterial wall they are exposed to immune cells and evoke an inflammatory response (Van Amersfoort et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide-protein complex (endotoxin) is an important constituent of the outer membrane of a P. multocida cell. Besides its toxic role in pathogenesis of the disease (Schimmel et al, 1982;Mendes et al, 1994;Kunkle and Rimler, 1998;Horadagoda et al, 2002), endotoxin is also immunogenic at low concentrations (Rimler and Phillips, 1986;Muniandy et al, 1998). LPS molecules are not toxic when they are bound to the bacterial outer membrane but after release from the bacterial wall they are exposed to immune cells and evoke an inflammatory response (Van Amersfoort et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous inoculation of lipopolysaccharide from serotype B:2 stains could reproduce clinical signs of haemorrhagic septicaemia in buffalo (Horadagoda et al , 2002), but the endotoxic properties of lipopolysaccharide from serotype A strains is less clear. Studies have indicated that chicken embryos and mice are highly susceptible, but that turkey poults are relatively resistant (Ganfield et al , 1976; Rhoades & Rimler, 1987; Mendes et al , 1994).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…multocida LPS is endotoxic, but its toxicity varies between hosts. LPS isolated from serotype B strains and administered intravenously into buffalo can mimic the clinical signs of hemorrhagic septicemia (Horadagoda et al 2002 ), but turkey poults were relatively resistant to the effects of LPS isolated from a serotype A strain (Ganfi eld et al 1976 ;Rhoades and Rimler 1987 ;Mendes et al 1994 ). In addition to different host responses, differences in the LPS structure in different serotypes may affect the nature and intensity of the innate immune response.…”
Section: Role Of Lps In Virulencementioning
confidence: 99%